The Relationship between the Nutritional Status and Intelligence among the Children in Selected Schools, Bengaluru - Lamichhane, Satya (Journal of Advanced Academic Research, 2023)
Background of the study Nutritional status is the condition of health of the individual as influenced by the utilization of the nutrient. It is concerned primarily with the part played the nutrients in body growth, development and maintenance. Good nutritional status means, maintaining a nutritional status that enables us to grow well and enjoy good health. Nutrition is a fundamental pillar of human life.Methods:  A Quantitative approach was used to assess the relationship between nutritional status and intelligence among the children. The research design adopted for the study was Non-experimental correlation research design. Sample of 60 schoolchildren were selected for the study using Probability –simple random sampling technique (lottery method). The modified conceptual framework for the present study was based on Fishbone model.Anthropometry measurement and cultural fair nonverbal intelligence test was used to collect the data from the study. The experts validated the tool for data collection and the reliability was established using test re-test method using Karl Pearson’s formula. Pilot study was conducted to determine the feasibility of the study following which the main study was done. Ethical and legal parameters were taken into consideration throughout the study. The main study was conducted Aryan presidency school, Nagarbhavi Bengaluru. Among children within age group 8-10.The data collected were analyzed and interpreted by using descriptive and inferential statistics.Result: The finding of the study showed that the finding of the study revealed that, the assessment of the nutritional by weight 51.5% (31) were in normal range, 21.7% (13) were mildly impaired, 5.0 % (3) were moderately impaired range and 21.7% (13) were severely impaired. The assessments of the nutritional status by height 73.3% (44) were in normal range, 16.7% (10) were mildly impaired, 10.0% (6) were moderately impaired range and no one were severely impaired. The assessment of the nutritional status by MUAC 76.7% (46) were in normal range, 23.3% (14) were Stunted and no one were Stunted and wasted. Intelligence level of the school children 10.0% (6) were very superior, 3.3% were superior, 16.7% (10) were high average, 56.7% (34) were average, 10.0% were low average, 1.7% (1) was borderline and 1.7% (1) was extremely low. The finding of intelligence test -1, the range was 1-12, Mean was 7.6, Standard deviation was 2.59 and Mean percentage was 63.33. With regard to test -2, the Range was 4-13, Mean was 7.8, SD was 2.31 and Mean percentage was 55.7. With regard to test-3 Range was 1-11, Mean was 6.8, SD was 2.34 and Mean percentage was 56.7. With regards to test -4 the Range was 0-8, Mean was 2.98, SD was 1.87 and Mean percentage was 37.3. The overall score of the intelligence Range was 13-39, Mean was 25.2, SD was 6.23 and Mean percentage was 54.8. Correlation between height and intelligence (r=0.344), weight and intelligence (r=0.397) and MUAC and intelligence (r=0.352) among the children. Hence, there is a positive correlation between the nutritional status and intelligent among children. Chi square test was used to find the association between nutritional status and intelligence among the school children with their selected demographic variables .the result of the Chi square analysis indicated that there is a significant association between the nutritional status and intelligence among school children with their selected demographic variables, such as nutritional status by weight and demographic variables among the school children and it was significant associate of type of family and Mother’s occupation, nutritional status by height and demographic variables among the school children and it was found significant associate of mother’s education, nutritional status by MUAC and demographic variables among the school children and it was significant associate of mother’s occupation, and intelligence level and demographic variables among the school children and it was significant associate of class studying.Conclusion: The present study attempted to assess the relationship between the nutritional status and intelligence among the children and found that positive relationship was between the nutritional status and intelligence among the children within age 8-10 years.